Recent improvements to the public finance block of the OECD's long-term global model - Guillemette, Yvan (OECD Economics Department Working Papers, 2019)
This paper documents recent extensions and revisions made to the model underlying the long-run global macroeconomic scenarios that are published every few years. First, a fiscal block is added for 11 countries that previously lacked one. Second, public pension expenditure projections are made endogenous to the projected ratio of retirees to workers and to a hypothesis on the future evolution of benefit ratios. Cross-country differences in projected public pension expenditure thus reflect many factors, including the speed of population ageing, the evolution of employment rates for older people, especially females, and rules regarding the evolution of statutory retirement ages. Third, revised public health expenditure projections introduce a higher income elasticity in middle-income than high-income countries and makes the excess of health care inflation over GDP inflation (Baumol effect) endogenous to the projected labour productivity growth rate. And fourth, the determination of long-term interest rates is revised to associate the fiscal risk premium to net, as opposed to gross, government debt, and make its size conditional on euro area membership, the quality of public governance and the occurrence of systemic banking crises, while allowing a flight-to-safety effect during such crises to lower bond yields in countries that are providers of global safe assets